Nonlinear longitudinal localized magnetoelastic waves in a plate in an arbitrarily oriented magnetic field - Erofeyev, Vladimir Ivanovich; Malkhanov, Alexey Olegovich (Computational Continuum Mechanics, 2012)
The influence of orientation of an external magnetic field on the characteristics of longitudinal magnetoelastic waves propagating in a homogeneous nonlinear elastic plate is studied. We estimate the relative degree of impact strength and orientation of the magnetic field on the parameters of the magnetoelastic wave.
Keywords: nonlinearity; localization; magnetoelasticity; longitudinal wave; arbitrary spatial orientation; magnetic field